Intravenous Metoclopramide to Improve the Success Rate of Blind Bedside Post-pyloric Placement of Feeding Tube in Critically Ill Children: A Randomized, Double-Blind, Placebo-Controlled Study - Ketsuwan, Sirima; Tanpowpong, Pornthep; Ruangwattanapaisarn, Nichanan; Phaopant, Supatra; Suppalarkbunlue, Nattanicha; Kooanantkul, Chula; Anantasit, Nattachai; Vaewpanich, Jarin (Frontiers in Pediatrics, 2021)
Objective: Impaired gastric emptying is a common cause of delayed feeding in critically ill children. Post-pyloric feeding may help improve feeding intolerance and nutritional status and, hence, contribute to a better outcome. However, post-pyloric feeding tube insertion is usually delayed due to a technical difficulty. Therefore, prokinetic agents have been used to facilitate blind bedside post-pyloric feeding tube insertion. Metoclopramide is a potent prokinetic agent that has also been used to improve motility in adults and children admitted to intensive care units. The objective of this study was to determine the efficacy of intravenous metoclopramide in promoting the success rate of blind bedside post-pyloric feeding tube placement in critically ill children. Design: Randomized, double-blind, placebo-controlled study. Setting: Single-center pediatric intensive care unit. Patients: Children aged 1 month-18 years admitted to the pediatric intensive care unit with severe illness or feeding intolerance were enrolled. Intervention: Patients were randomly selected to receive intravenous metoclopramide or 0.9% normal saline solution (the placebo) prior to the tube insertion. The study outcome was the success rate of post-pyloric feeding tube placement confirmed by an abdominal radiography 6-8 hours after the insertion. Measurements and Main Results: We found that patients receiving metoclopramide had a higher success rate (37/42, 88%) of post-pyloric feeding tube placement than the placebo (28/40, 70%) (P= 0.04). Patients who received sedative drug or narcotic agent showed a tendency of higher success rate (P= 0.08). Conclusion: Intravenous metoclopramide improves the success rate of blind bedside post- pyloric placement of feeding tube in critically ill children.